2022
DOI: 10.5114/biolsport.2022.107483
|View full text |Cite
|
Sign up to set email alerts
|

Combined training is not superior to strength and aerobic training to mitigate cardiovascular risk in adult healthy men

Abstract: Although the beneficial effects of aerobic training on cardiovascular risk factors are evident, the potential beneficial effect of strength and combined training on these risk factors is controversial. This study aimed to evaluate the effect of aerobic and strength training programmes, performed alone or in combination, on cardiovascular risk factors in sedentary, apparently healthy and non-obese adult men. The study was conducted with 37 subjects who were randomly divided into the following groups: aerobic (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Of these, 9 studies start the exercise session with resistance exercise followed by aerobic exercise 16 , 32 , 35 , 36 , 38 , 55 , 64 , 65 , 68 , and 6 studies started the exercise session with aerobic exercise followed by resistance exercise 33 , 37 , 57 , 59 , 66 , 67 . One study combined aerobic and resistance exercise in the same session, however, the order of exercises was alternated each week 61 and another study involved a mixed circuit training methodology 34 . Another study 63 reported that aerobic exercise was followed by resistance exercise, however, it is not clear if was performed on the same day or on separate days.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 9 studies start the exercise session with resistance exercise followed by aerobic exercise 16 , 32 , 35 , 36 , 38 , 55 , 64 , 65 , 68 , and 6 studies started the exercise session with aerobic exercise followed by resistance exercise 33 , 37 , 57 , 59 , 66 , 67 . One study combined aerobic and resistance exercise in the same session, however, the order of exercises was alternated each week 61 and another study involved a mixed circuit training methodology 34 . Another study 63 reported that aerobic exercise was followed by resistance exercise, however, it is not clear if was performed on the same day or on separate days.…”
Section: Resultsmentioning
confidence: 99%